Features of Picea abies (L.) Karst. population structure formation on the territory of Belarus - Padutov, Vladimir E. (Experimental Biology and Biotechnology, 2021)
One of the main forest forming tree species in Belarus is the European spruce (Picea abies (L.) Karst.). The formation of European spruce forest population genetic structure took place under the influence of migration flows from different refugia during the postglacial period. For the genogeographic study of P. abies 25 isozyme genes (Aat-1, Aat-2, Adh, Gdh, Idh-1, Idh-2, Mdh-1, Mdh-2, Mdh-3, Skdh, 6-Pgd-1, 6-Pgd-2, 6-Pgd-3, Lap-1, Lap-2, Sdh, Gpi, Hk, Me, Dia-1, Dia-2, Dia-4, Pgm-1, Pgm-2, Fl-Est) of nuclear DNA (analysis was carried out in 10 populations), 3 microsatellite loci (Pt63718, Pt26081, Pt71936) of chloroplast DNA (57 populations were considered) and 1 microsatellite locus (mt15-D02) of mitochondrial DNA (56 populations were studied) were used. As a result, 82 allelic variants of isozyme genes, 19 allelic variants of chloroplast DNA loci and 2 allelic variants of mitochondrial DNA locus were found. The spatial distribution of the alleles was defined and the regional features of the genogeographic differentiation of the spruce forest were considered. The presence of two migration flows representatives (southern and northern) in Belarus was confirmed. It was shown that the highest concentration of P. abies trees with southern (Carpathian) origin is observed in the southwest of the country. Clinal variability was revealed for a number of markers in the directions from south to north and from west to east. In general the data obtained are consistent with the results of studies based on the analysis of the spatial distribution of the cone scales traits.